Being where the users are: Readiness of academic librarians to satisfy information needs of users through social media. Issue 8 (7th November 2016) - Ahenkorah-Marfo, Michael; Akussah, Harry
Abstract : Purpose: The purpose of this research is to investigate the preparedness of academic libraries in Ghana for the use of social media in reference and user services. Design/methodology/approach: A qualitative research approach using interviews was used to solicit the views of Systems/reference librarians from six most highly ranked public and private universities (in Ghana) on their libraries' preparedness for use of social media to provide reference and user services. Findings: The findings of the study indicate that most of the university libraries lacked policy on the use of social media and that though librarians held the perception that social media was useful, they lacked the competence and motivation to use social media to make a remarkable difference in service delivery. Practical implications: Academic libraries in Ghana and elsewhere will find the results useful in formulating policies for the use of social media in libraries. Originality/value: This qualitative approach to the study of social media deviates from the mostly quantitative studies in the literature and has brought out more revealing findings.